Tool Support for Spectrum-based Fault Localization during Continuous Integration - Silva, Erickson Lima Barbosa da; Araujo, Roberto Paulo Andrioli; Chaim, Marcos Lordello (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
Program debugging is one of the most time consuming activities carried out by developers because, in large extent, it is performed in ad hoc fashion. Significant research efforts have been directed to the development of new debugging techniques, in special, fault localization techniques. Spectrum-based Fault Localization (SBFL) is a debugging technique that has been experimented on programs similar to those developed in industry with promising results. To support the automated application of SBFL, tools have been developed, yet in the academic realm. Few of them, though, aim to support SBFL in the context of the Continuous Integration (CI) practice. We present the Jaguar Portal platform, designed and developed to receive, store, and provide access to SBFL information in CI environments. The platform encampsulates the Jaguar 2 tool, which is responsible for executing the SBFL technique during the build process in the CI pipeline on GitHub. Furthermore, it provides web interfaces that display SBFL analyses with code snippets and suspicious line markings.We believe Jaguar Portal is a step towards the adoption of SBFL techniques in industrial settings. Demo video: https://www.youtube.com/@JaguarPortalSBFL .